2017
DOI: 10.1136/bmjopen-2016-014979
|View full text |Cite
|
Sign up to set email alerts
|

Is vaginal breech delivery associated with higher risk for perinatal death and cerebral palsy compared with vaginal cephalic birth? Registry-based cohort study in Norway

Abstract: ObjectiveThis paper aims to study if vaginal breech delivery is associated with increased risk for neonatal mortality (NNM) or cerebral palsy (CP) in Norway where vaginal delivery accounts for 1/3 of all breech deliveries.DesignCohort study using information from the national Medical BirthRegister and Cerebral Palsy Register.SettingBirths in Norway 1999–2009.Participants520 047 term-born singletons without congenital malformations.Main outcome measuresNNM, CP and a composite outcome of these and death during b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 39 publications
2
40
0
2
Order By: Relevance
“…We confirm that a trial of vaginal breech labor is associated with adverse short-term outcomes. Our findings regarding the perinatal mortality rate are consistent with earlier studies [21,31] that have shown that the perinatal mortality rate in planned vaginal breech delivery is higher than in planned cesarean breech delivery. The infants from the trial of vaginal labor group had a lower 5-min Apgar score and a lower umbilical artery pH, as shown before [4,5,32,33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We confirm that a trial of vaginal breech labor is associated with adverse short-term outcomes. Our findings regarding the perinatal mortality rate are consistent with earlier studies [21,31] that have shown that the perinatal mortality rate in planned vaginal breech delivery is higher than in planned cesarean breech delivery. The infants from the trial of vaginal labor group had a lower 5-min Apgar score and a lower umbilical artery pH, as shown before [4,5,32,33].…”
Section: Discussionsupporting
confidence: 93%
“…After the exclusion of pregnancies with other risk factors for adverse neurodevelopment, no correlation between vaginal breech delivery and the risk of adverse neurological development like cerebral palsy or epilepsy, as shown by Krebs et al [17,18], was identified. Our results regarding the lack of excess risk for adverse neurological development associated with vaginal breech labor are consistent with the results of a recently published large Norwegian population based cohort study [31] and with the followup study of the term breech trial [14], which reviewed the children from the term breech trial at 2 years of age and could not find a difference regarding the risk of death or risk of neurodevelopmental delay between the planned cesarean birth group (3.1%) and the planned vaginal birth group (2.8%) [14].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, children born by vaginal breech delivery ( n = 41, 0.37%) and whose mode of delivery was unknown ( n = 4, 0.04%) were also excluded, leaving 11,049 (99.2%) mother-infant pairs at baseline. Children born by vaginal breech delivery were excluded as they may differ from those born by vaginal cephalic delivery in important ways, for instance, they have a higher neonatal mortality rate 34 , moreover, we did not have enough numbers to include them as a separate category. Further details regarding the GUI study have been reported previously 31 – 33 .…”
Section: Methodsmentioning
confidence: 99%
“…78 Some centres are now offering carefully screened women the option of trying for a vaginal breech birth, with generally good outcomes. 79 Women with a previous CS but who have no complications in a subsequent pregnancy, are often offered a trial of labour with a view to achieving VBAC. The only trial of VBAC in the relevant Cochrane review includes data on mode of birth for just 22 women, with no significant difference in CS rates.…”
Section: Clinical Interventionsmentioning
confidence: 99%